Scooby-Doo! on werewolf watch - Sander, Sonia; Duendes Del Sur (Firm) (New York : Scholastic, 2012)
There's a werewolf hiding in Pippa's Pet Shop! Can Scooby get a leash on that creepy canine?
"250-750 words."
1-2.
520
Accelerated Reader AR
Keywords: Scooby-Doo -- (Fictitious character) -- Juvenile fiction; Scooby-Doo -- (Fictitious character) -- Fiction; Werewolves -- Juvenile fiction; Werewolves -- Fiction; Readers -- Juvenile fiction